Context influences the interplay of endocrine axes across the day. Issue 6 (27th June 2015) - Dismukes, Andrew R.; Shirtcliff, Elizabeth A.; Hanson, Jamie L.; Pollak, Seth D.; Shirtcliff, Elizabeth A.
ABSTRACT The current investigation examined stressors upon the coupling of the hypothalamic–pituitary–adrenal (HPA) and hypothalamic–pituitary–gonadal (HPG) axes. Emphasis is placed on the moderating role of context and time. One hundred and eighteen adolescent males and females provided up to 32 diurnal saliva samples across a visit to a research lab. This visit constituted a day‐long stress through which the impact on HPA–HPG axis coupling could be assessed. We tested four models of HPA–HPG axis coupling across the lab day. Sex and stress hormones operated synchronously (β = .404, p < .001), and the coupling of sex and stress hormones was moderated by the stress of the lab day (β = .010, p = .05). This pattern of co‐elevation did not appear to be moderated by the distal experience of early life adversity. Findings suggest that the notion of "stress" must disentangle proximal and distal challenges, each of which appears to impact neurobiological processes. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 57: 731–741, 2015.